Effects of Educational Video on Pre-operative Anxiety in Children - A Randomized Controlled Trial - Härter, Valentina; Barkmann, Claus; Wiessner, Christian; Rupprecht, Martin; Reinshagen, Konrad; Trah, Julian (Frontiers in Pediatrics, 2021)
Objective: Audio-visual interventions have been used to provide relevant patient information to reduce preoperative anxiety in children. The aim of the study was to investigate whether self-reported state anxiety in children could be reduced by presenting a child-friendly educational video on the day of surgery. Methods: A prospective, single-blinded, two-armed, randomized controlled study was designed with three measurement time points including 90 children (6–17 years) and their parents. In the intervention group (IG), the children and their parents were shown a child-friendly video explaining the perioperative procedures that would be applied during the hospital stay, in addition to receiving standard information. In the control group (CG), children and parents received standard information provided by the nursing staff. The primary outcome was any change in the children’s preoperative state anxiety levels, as measured by the State-Trait Operation Anxiety Inventory (STOA). A secondary outcome was patient satisfaction regarding the received information. Results: Anxiety was significantly reduced in both groups after receiving either the intervention plus standard information or the standard information only. No significant difference in anxiety reduction was observed between the IG and the CG. However, the children and parents in the IG reported fewer worries than those in the CG. Conclusion: A child-friendly, educational video can be an additional tool for providing patient information and reducing preoperative anxiety in children and their parents. Further studies should focus on the timing of the intervention and on age- and developmentally appropriate information formats and contents to address children’s preoperative anxiety.